THE EFFECT OF FAMILY FUNCTIONING AND FRIENDSHIP QUALITY ON SELF-IDENTITY FORMATION IN LATE ADOLESCENTS WITH DUAL-EARNER PARENTS: Pengaruh Keberfungsian Keluarga dan Kualitas Pertemanan Terhadap Pembentukan Identitas Diri pada Remaja Akhir dengan Orang Tua Dual-Earner - Wijaya, Rio Natannael; Setiawan, Jenny Lukito (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The shift in modern family structures has led to a rise in dual-earner families, potentially influencing identity formation in late adolescents. This study aims to investigate the effects of family functioning and friendship quality on identity formation among late adolescents from dual-earner families. A quantitative approach was employed, involving 109 late adolescents aged 15–21 years in Surabaya whose parents work full-time. Instruments included the Family Assessment Device – General Functioning Scale, the Friendship Quality Scale, and the Dimensions of Identity Development Scale (DIDS). Data were collected via a Google Form and analyzed using multiple linear regression. The results showed that family functioning and friendship quality jointly had a significant effect on identity formation (F = 806.912; p < 0.05). However, individually, only friendship quality demonstrated a significant impact (p < 0.01), while family functioning did not (p > 0.05). These findings highlight the pivotal role of friendship quality in supporting identity exploration and commitment among late adolescents in the context of limited family interactions in dual-earner households.